Tensile Properties and Manufacturing Defectives of Short Carbon Fiber Specimens Made with the FDM Process - Blaj, Madalina; Zaharia, Sebastian-Marian; Pop, Mihai Alin; Oancea, Gheorghe (Materiale Plastice, 2022)
With the fourth industrial revolution, Additive Manufacturing started to offer new possibilities of manufacturing, Fused Deposition Modeling being one of the most used processes for fabrication. In this paper, the studied specimens are manufactured based on the Fused Deposition Modeling (FDM) method, with a filament of short carbon fiber and polyethylene terephthalate (PET) matrix, with a variation of the layer thickness. For the resulted specimens the tensile properties are determined according to ASTM D638. The most advantageous results are obtained for the layer thickness of 0.15 mm, with the tensile strength of 58 MPa. Based on the stress-strain curves which are presented in this paper, it also can be assumed that the material is brittle. The results of the mechanical properties are very similar for each group of specimens and it can be assumed that the mechanical properties are homogenous due to the material quality and the machine performances. For all the specimens the rupture location is almost in the same area. Due to the difficulty of carbon fiber filament printing, the manufacturing defectives which appear during the manufacturing process are detected, the most common manufacturing defectives being the material gaps from each specimen, which are identified with microstructural analysis. As failure modes, the most common failure criteria are the delamination and the matrix cracks.
Keywords: additive manufacturing; fused deposition modeling; short carbon fiber; tensile test